THE EFFECT OF CONCEPT ORIENTED READING INSTRUCTION (CORI) STRATEGY TOWARD STUDENTS’ READING COMPREHENSION - Umi Kalsum; BAMBANG SUWARNO; I Wayan Dharmayana (JOALL (Journal of Applied Linguistics and Literature), 2017)
The purpose of this study is to find the effect of CORI (Concept-Oriented Reading Instruction)strategy on students’ reading comprehension. This reseach was focused on whether CORI  strategy affected students’ reading comprehension. This research employed a quasi-experimental design. The subjects comprised 48 students of grade VIII of SMPN 4 Kota Bengkulu, divided into two classes, the experiment and control class. The instrument was a reading test. The result showed that CORI strategy was effective to improvestudents’ reading comprehension. In addition, the students also had positive attitudes toward the use of CORI strategy. It is recommended to conduct an experiment for another school level